Embedded Based Vehicle Speed Control System Using Wireless Technology: - (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The research focus on unifying the Global Positioning system with embedded wireless system is the new approaches in intelligent vehicle control for critical remote location application using ARM. In conventional system they are designed to control the speed of vehicles in all days. The main objective of the proposed system is to operate the vehicle in safe speed at critical zones. The base station having the transmitter which is designed for Frequency Modulation (FM), the receiver part is implemented in Vehicle. The ARM processor is implemented at receiver side, which receives the critical frequency, and then it is activated in critical mode. Speed Control Driver (SCD) can be custom designed to fit into a vehicle’s dashboard, and displays information on the vehicle. Once the information is received, it automatically alerts the driver, to reduce the speed according to the time and zone. The novel system is implemented with the support of embedded processor and the simulation is achieved through Keil C software and results are discussed.